IMPLEMENTASI TRAKTAT MARRAKESH TERHADAP PENYANDANG DISABILITAS NETRA DALAM MENGAKSES INFORMASI KARYA CETAK: IMPLEMENTATION OF THE MARRAKESH TRACT ON PERSONS WITH DISABILITIES NETRA IN ACCESSING PRINTED WORK INFORMATION - Ondrey, Muh. Luky; Hasan, Yulia A.; Oner, Basri (Clavia, 2022)
This study aims to find out: 1) How is the implementation of the Marrakesh Treaty to personswith blind disabilities for accessing information on printed works in Indonesia; 2) Factors thathinder persons with blind disabilities for accessing information of printed works in Indonesia.The research method used is empirical normative. Research location in Makassar City. Datacollected by literature study method and interview. The results showed: 1) Marrakesh Treatywas implemented in Law Number 28 of 2014 which was further regulated in GovernmentRegulation Number 27 of 2019 which was perfected by ratifying the Marrakech Treaty in theform of Presidential Regulation Number 1 of 2020, although the implementation in thecommuinty is constraind by the Covid-19 pandemic; 2) Factors that hinder persons with blinddisabilities for accessing information of printed works in Indonesia are limited availability ofaccessible books or printed works, the existence of copyright barriers in converting basic booksinto book formats that can be accessed by peoples with visual impairments, and the absence ofexternal institutional support to fight for the rights of persons with visual impairments inIndonesia.